Optimalisasi Supervisi Akademik Kepala Sekolah Sebagai Upaya Peningkatan Kompetensi Profesional Guru Dalam Kehadiran Mengajar Pada Semester Juli-Desember 2022 Di SD Negeri 05 Serasi, Kec. Rao Selatan Kab. Pasaman - Ahmad Irwan (Bakaba, 2022)
In SD Negeri 05 Serasi, Rao Selatan District, the academic supervision of school principals will be optimized with the goal of enhancing teachers' professional competence. The PTS was conducted during the summer semester of 2022 at SD Negeri 05 Serasi in Kecamatan Rao Selatan. All of the teachers of SD Negeri 05 Serasi in Kecamatan Rao Selatan made up the analysis' unit. the action is carried out utilizing the cycle model created by Chemmis and MC Taggart. The teacher's presence in the classroom during PBM is the variable that was observed. According to the study's findings, teacher attendance at SD Negeri 05 Serasi in the Rao Selatan District averaged 68.75% from July to September and 95.83% from October to December. There was a 27.08% increase. The Overachieving the success target is the average teacher attendance in class. Based on data analysis, it has been determined that at SD Negeri 05 Serasi in the Rao Selatan District, good principal supervision can enhance the discipline of teacher attendance in class.